Same-day versus delayed simulation imaging after placement of a perirectal hydrogel spacer for prostate radiotherapy - Fredman, Elisha; Weinstock-Sabbah, Miriam; Icht, Oded; Moore, Assaf; Shochet, Tzippora; Limon, Dror; Bragilovski, Dimitri (Frontiers in Oncology, 2023)
Introduction Placement of a perirectal hydrogel spacer has been demonstrated to reduce the risk of rectal toxicity from prostate radiation. Practices vary regarding timing of CT-simulation after hydrogel placement, and the ideal schedule remains unknown. Methods Thirty patients with localized prostate adenocarcinoma underwent trans-rectal ultra-sound-guided placement of an iodinated SpaceOARTM hydrogel prior to radiotherapy. Per evolving practice, fifteen completed same-day simulation and fifteen returned for simulation 1-2 weeks later. Hydrogel volume, perirectal distance, air-void volume, and rectal dosimetry per NRG GU005 were compared between CT-simulation, 1st-fraction Cone-Beam-CT (CBCT), and final CBCT. Results CT-simulation occurred 8.8 ± 2.4 days after placement in the delayed group, with no significant difference in the interval between simulation and 1st-fraction between groups (p=0.165). Greater observed de-creases in hydrogel volume (0.57cc vs. 0.04cc, p=0.0002), and perirectal distance at both mid-gland (1.32mm vs. 0.17mm) and tallest point (2.40mm vs. 0.04mm) were seen on 1st-fraction CBCT in the same-day group (p=0.0039; p=0.0002). Per dosimetry recalculated on 1st fraction CBCT, five (D3cc and D50%) vs. one (D50%) rectal dose parameters were exceeded in the same-day and delayed groups, respectively, and 10 vs. one parameters had a relative increase of ≥20%. Conclusions Due to the evolving anatomic changes in the days following hydrogel placement, same-day simulation scanning may introduce unintended variability in rectal dosimetry at the time of prostate radiotherapy.